The Firebrand: Clay Center, Clay County, Kansas; December 1883-November 1884 - Collins, Becky (Kansas State University, The Chapman Center for Rural Studies, 2010)
Among the 713 newspapers in print in Kansas in the 1880s, a single short-lived newspaper provides insight into political shifts and battles in small towns. The Firebrand newspaper in Clay Center provided inflammatory rhetoric for a single year, also switching political sides from Republican to Democrat. This is an in-depth study of one newspaper; the author, a journalism major, read every issue and perceptively analyzes tone, message, and content.
Becky Collins, “The Firebrand: Clay Center, Clay County, Kansas; December 1883-November 1884,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/213.